Reading Skills: Prospects, Issues and Challenges - Sudha, S. T.; Harinarayana, N. S. (Journal of Information and Knowledge, 2008)
This article deals with the concepts, prospects, issues and challenges pertaining to reading skills. It also deals with the relevance of reading in the Internet era. It stresses the need for the role of libraries in promoting the reading skills of the youth, and issues pertaining to their reading behavior. The librarian plays an important role in developing the reading skills of the children and youngsters, along with the encouragement given by teachers and parents. It deals with educational, political, social, and economical issues. It is of utmost need to organize umpteen numbers of activities in promoting positive attitude towards reading which paves the way for intensive learning. This article deals with the concepts, prospects, issues and challenges pertaining to reading skills. It also deals with the relevance of reading in the Internet era. It stresses the need for the role of libraries in promoting the reading skills of the youth, and issues pertaining to their reading behavior. The librarian plays an important role in developing the reading skills of the children and youngsters, along with the encouragement given by teachers and parents. It deals with educational, political, social, and economical issues. It is of utmost need to organize umpteen numbers of activities in promoting positive attitude towards reading which paves the way for intensive learning.